Monthly changes in some reproductive parameters and in testosterone and thyroxine values of rams throughout one year under continental climate conditions - Gundogan, M; Demirci, E (M H Schaper Gmbh Co Kg, 2003)
Ten sexually mature rams were used in this study. Blood and semen was collected monthly from rams for one period of 12 months to study semen characteristics and to determine serum testosterone and thyroxine (T-4) hormones. Results showed that all of the rams are continuous breeders as they show sexual desire and produce semen throughout the whole year. However, monthly variations in reproductive and semen characteristics were detected. Relative testes volume, ejaculate volume, sperm motility, sperm concentration and serum testosterone levels were higher during autumn months than at other months of the year. In addition, autumn months showed moderate percentage of abnormal spermatozoa. Furthermore, serum T4 was significantly higher in summer and autumn months than that observed in winter and spring. These results indicate that ram semen quality in Afyon continental climate conditions may be better during late summer and early autumn months than during other months of the year.
Keywords: hormone; month; ram; semen